REALITAS PESINDEN DALAM SUDUT PANDANG INDUSTRI BUDAYA OLEH ADORNO DAN HORKHEIMER - Gutami Hayu Pangastuti (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2025)
In Javanese karawitan, sindhen plays the role of presenting the music. This activity is referred to as nyindhen with the aim of strengthening the character of the gendhing. The sindhen is not categorized as a solo singer, but rather as part of the instrument, marking her role as not a soloist. Over time, the role of pesinden, especially in pakeliran music, has grown. This is especially true when wayang offerings are expanded through television broadcasts and digital platforms. The public is increasingly familiar with and fond of wayang, especially because of the existence of creativity that is increasingly developed. Instead of introducing the arts of the archipelago, with or without realizing it, it shifts the function and essence of the art actors. So, how does the cultural industry have an involvement in shaping the realm of work of puppeteers? What phenomena are captured from the reality of courtesans in the perspective of the cultural industry? Through analysis with the approach of Adorno and Horkheimer in the Dialectic of Enlightment published by Standford University Press in 2022, it presents a critical point of view around the dialectic of enlightenment including the cultural industry. Using the webtography method, the observation of the data summarized through the article includes two elements, namely the singer and the reality of her work in the cultural industry and the motive of reality as an impact of mass products. The article becomes a form of offer from the description of the reality of the singer who personally conveys an image that cannot be separated as a form of creation.